KOMUNIKASI RITUAL DALAM TRADISI MAKAN NASI KETAN PADA ADAT PERNIKAHAN SUKU LEMBAK DI KOTA BENGKULU - M. Ridho Syabibi; Tarmizi; Hawasi (DECODING: Jurnal Mahasiswa KPI, 2026)
Abstract This study examines ritual communication in the Makan Nasi Ketan tradition within the wedding customs of the Lembak ethnic community in Bengkulu City. The tradition is performed after the engagement process and constitutes an important stage in the sequence of traditional wedding ceremonies. This study aims to understand the communication practices involved and how the community interprets the cultural elements embedded in the tradition. Using an ethnography of communication approach with qualitative methods, this research provides an in-depth description of cultural practices, social interactions, and meanings constructed among community members. Data were collected through observation, in-depth interviews with traditional leaders and involved families, and documentation. The findings indicate that the Makan Nasi Ketan tradition functions as a collective communication space for both families to deliberate, build mutual understanding, and distribute roles and responsibilities in preparing for the wedding. In addition, sticky rice (nasi ketan) is understood by the community as representing the hope for close, harmonious, and enduring relationships. Thus, this tradition is not only part of customary practices but also serves as a form of cultural communication that strengthens social relationships and sustains cultural values within the Lembak community in Bengkulu City.